The new webster's international encyclopedia : the new illustrated reference guide - Harkavy, Michael D. (Naples, Florida : Trident Press International, 1999)
A concise, general-subject encyclopedia with color and black-and-white illustrations, maps and charts
Earth facts -- maps and index -- illustrated survey of world history -- declaration of independence -- U.S. Constitution -- Presidents of the United States -- U.S. Supreme Court Justices -- national parks -- Chemical elements -- periodic table of elements -- metric conversion table
Keywords: ENCYCLOPEDIAS AND DICTIONARIES